Impact of A Mobile Health Intervention On Bullying Among Children: A Systematic Review - Devis Yulia Rohmana; Ah Yusuf; Rr Dian Tristiana (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Bullying is an anti-social behavior carried out by individuals or type of aggressive behavior that contains intentional aspects to dominate and hurt others and caused negative impact on the victim's physical and psychological. Imbalance of strength, whether physical, age, and social status, which is done repeatedly by one or several children against other children is a characteristic of bullying behavior. This study aimed to evaluate the effectiveness of mHealth on bullying among children. The studies using PRISMA and searched in four databases that published between 2016 until 2020. Twelve articles found were used in this systematic review that contains about an antibullying program that involves several parties has the preventive efforts in cases of bullying. A majority of interventions can be used in bullying and also be used as promotive and preventive efforts in cases of bullying in schools and communities.